Trainability of junior Rugby Union players - Hendricks, S (South African Journal of Sports Medicine, 2012)
Growing interest in producing expert performance, and increasing sport participation, has led to a number of models being proposed for optimal sporting development. Using physical or psychological developmental milestones as guidelines, these models in sport were aimed primarily at identifying key stages during childhood and adolescence, and to optimise training adaptation for the child to reach his/her full sporting potential. Taking into consideration the long-term developmental models, and the requirements to succeed in rugby, this review aims to prescribe the trainability of junior rugby players using a scientifically evidence-based long-term player development approach. As there have been several recent and comprehensive reviews of the literature on trainability during childhood and adolescence, the aim of this paper is to resynthesise the material and apply it to rugby. Although athlete developmental models suggest that the appropriate application of training stimulus during specific periods in childhood and adolescence will influence athletic potential, recent available literature contends that this concept is inconclusive and requires further investigation.